Functional Outcomes of Non-operative Treatment in Proximal Humeral Fracture of Adults - Shahani, Mehtab Ali (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The functional outcomes after non-operative treatment of proximal humeral fractures in adults required detailed understanding for improved health outcomes. Objective: To identify the functional outcomes of non-operative treatment in proximal humeral fracture of adults. Study Design: Prospective cohort study Place and Duration of Study: Department of Orthopaedic, KMC Civil Hospital, Khairpur Mirs from 1st October 2020 to 30th September 2021. Methodology: Fifty patients with proximal humeral fracture >45 years were treated with non-operative treatment protocol including 1 year follow-up. Patient’s radiological imaging was continued till one year and they were given a sling to wear for three week’s time. The treatment primary functional outcomes were assessed by Oxford Shoulder Score and EuroQol-5 Dimensions-3 Levels, while secondary functional outcomes were assessed by visual analog scale and university of California Los-Angeles scoring method. Results: Mean age was 65.6±4.2 years with females as 74% and 26% males. Improvement in OSS was up to 48 points. One-year scores for OSS were mean 33.1 with 95% confidence of interval while it was 0.59 for EQ-5D-3L. Mean VAS pain score was 32.1 with 59.2 as VAS satisfaction score and UCLA activity score as 20.4. Conclusion: Non-operative treatment for proximal humeral fracture in adults’ results in significant changes in shoulder-specific as well as improved health outcomes after one year.